Stable Isotope Analysis of Dermis and the Foraging Behavior of Whale Sharks at Ningaloo Reef, Western Australia - Marcus, Lara; Virtue, Patti; Nichols, Peter D.; Ferreira, Luciana C.; Pethybridge, Heidi; Meekan, Mark G. (Frontiers in Marine Science, 2019)
In order to examine the foraging behavior of whale sharks at Ningaloo Reef in Western Australia, stable isotope analysis of the dermis was used to estimate 13C and 15N values. These were compared to isotope values obtained from likely species of local prey. Ontogenetic and sex-related variations in the isotopic composition of dermis were also examined. The 13C values of zooplankton and nektonic taxa at Ningaloo ranged from -18.9‰ to -16.5‰ reflecting the different carbon sources entering the food web (from a pelagic to a more inshore and benthic productivity). The isotopic composition suggests that whale sharks had greater reliance on pelagic primary and secondary productivity over a period of 3 years. Whale shark isospace matched some of the potential prey at Ningaloo Reef including krill, zooplankton and polychaetes. Consistency on 13C values indicated regional foraging ranges across the Ningaloo Reef area and the western Australian coast. More variability in 15N values showed, however, the different patterns of foraging among whale sharks. There was evidence of enrichment in 15N occurring with increasing size in male and female whale sharks, a pattern that could have been due to changes in growth rate and trophic level with age and/or an ontogenetic shift in feeding grounds. Our study brings new insights into the diet and feeding habits of an important whale shark population over large temporal and spatial scales in the eastern Indian Ocean. Such temporal and spatial information is essential for a better conservation management of this highly migratory and elusive species.